Extração assistida por ultrassom e micro-ondas dos compostos bioativos do bagaço e cascas de manga (Mangifera indica) : caracterização química e avaliação antioxidante - Oliveira, Julio Manoel Andrade (2023)
Mango (Mangifera indica) is a fruit worldwide consumed in natura, in juices, jellies and ice cream. However, its processing generates a significant amount of waste, considered an environmental problem. This work aimed to study the reuse of industrial mango waste (bagasse and peel) through the extraction of its bioactive components using extraction techniques with environmentally friendly solvents, as a way of directing this material to other more useful purposes. Ultrasoundassisted extraction (UAE) and Microwave-assisted extraction (MAE) were applied in order to obtain extracts with higher biological activities and yields, being directly compared with maceration extraction. Identification of bioactive compounds was performed using high-resolution mass spectrometry, followed by antioxidant activities. The optimization by EAU was carried out using the response surface methodology (RSM), which resulted in the optimal extraction condition using an ethanol concentration of 58.28%, solvent to solute ratio of 7.929 mL to 0.2 g, time of 5 min, frequency of 37 kHz, temperature of 40 ºC and 30% power. The optimal EAM condition, obtained by RSM, was ethanol concentration of 48.981%, time of 11 minutes and 6 s, solvent to solute ratio of 16 mL to 0.2 g, temperature of 84 ºC and power of 500W. Under these conditions, the yield obtained for the mango bagasse extract by UAE was 38.07% and the total phenolic content (TPC) was 101.63 mg EAG/g dw, values greater than those for the peel extracts of mango (36.07% and 92.95 mg EAG/g dw). The MAE extract from the bagasse resulted in a yield of 48.01% and TPC of 124.96 mg EAG/g dw, and for the peels they were 38.86% and 102.16 mg EAG/g dw, respectively. The extracts obtained by MAE showed higher values of yields, TPC and TFC compared to the UAE extracts. Antioxidant assays demonstrated that MAE extracts showed greater inhibition potentials compared to UAE extracts. In this work it was possible, by using Mass Spectrometry, to propose 39 chemical markers in the bagasse extracts and 28 for the peels extracts.